1986
DOI: 10.1073/pnas.83.9.2919
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of human neutrophils is immediately preceded by a large increase in cytoplasmic free calcium.

Abstract: When human polymorphonuclear leukocytes (PMN) are placed on various surfaces, they attach and spread rapidly, increasing their diameter severalfold. The spreading is associated with extensive changes in the cytoskeleton. Since many cytoskeletal events are regulated by Ca2 , we measured the cytosolic free calcium concentration ([Ca2+] Polymorphonuclear leukocytes (PMN) and macrophages placed on a variety of surfaces rapidly adhere and spread themselves out thinly on the surface (1, 2). This is thought to repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 23 publications
3
61
1
Order By: Relevance
“…GSD I b MDM did not show cytoplasmic spreading or morphologic alterations concomitant with monocyte differentiation unless cultured in the presence of IFN-y, which then resulted in morphologic changes similar to control cells. After adherence, a rise in intracellular Ca2+, similar to that in respiratory burst activity, is a necessary precedent to spreading in neutrophils (45). We have previously demonstrated depressed Ca2+ mobilization in GSD Ib monocytes that is associated with decreased intracellular Ca2+ stores.…”
Section: Resultsmentioning
confidence: 99%
“…GSD I b MDM did not show cytoplasmic spreading or morphologic alterations concomitant with monocyte differentiation unless cultured in the presence of IFN-y, which then resulted in morphologic changes similar to control cells. After adherence, a rise in intracellular Ca2+, similar to that in respiratory burst activity, is a necessary precedent to spreading in neutrophils (45). We have previously demonstrated depressed Ca2+ mobilization in GSD Ib monocytes that is associated with decreased intracellular Ca2+ stores.…”
Section: Resultsmentioning
confidence: 99%
“…Existing data provide clear evidence that neutrophil polarization is linked to intracellular Ca 2+ mobilization (31)(32)(33).…”
Section: Intracellular Storagementioning
confidence: 99%
“…Pioneering work by Maxfield showed that the spreading of neutrophils and macrophages onto surfaces is preceded by large global cytosolic free Ca 2+ signals (Kruskal et al, 1986: Kruskal andMaxfield, 1987). These cytosolic free Ca 2+ signals were caused by adhesive signals to the cell from the substrata, and it has subsequently been shown that immobilisation of b2 integrin by surfaces (Jaconi et al, 1991;Pettit and Hallett, 1996) or cross-linking by anti-integrin antibodies (Ng-Sikorski et al, 1991: Petersen et al, 1993 triggers similar Ca 2+ signals.…”
Section: Introductionmentioning
confidence: 99%